47th AIAA Fluid Dynamics Conference 2017
DOI: 10.2514/6.2017-3976
|View full text |Cite
|
Sign up to set email alerts
|

Theory and validation of a 2D Finite-Volume integral boundary layer method intended for icing applications

Abstract: Nomenclature C D viscous dissipation coefficient C f friction coefficient f, g, l closure functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The solved equations which were presented are an extension of the 2D system of equations of Bayeux et al 3 The unsteady momentum and kinetic energy equations are written in conservation form. Regarding heat transfer, a 2D-like approach is used to infer the heat transfer coefficient from the dynamics of the boundary The solver is based on the Finite Volume method, using an upwind scheme, which was presented in the present paper.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The solved equations which were presented are an extension of the 2D system of equations of Bayeux et al 3 The unsteady momentum and kinetic energy equations are written in conservation form. Regarding heat transfer, a 2D-like approach is used to infer the heat transfer coefficient from the dynamics of the boundary The solver is based on the Finite Volume method, using an upwind scheme, which was presented in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…At least for usual (and simple enough) closure relations, it can be demonstrated that the IBL equations are hyperbolic. 3,4 This allows to define stable spatial discretization schemes. This also makes the Finite Volume Method a good choice for the resolution of the IBL equations.…”
Section: Derivation Of the Model Iia Brief State-of-the-art Of 3dmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the framework of the development of ONERA's icing suites IGLOO2D [7,8] and IGLOO3D [9], which involve a large number of cycles of a flow solver, different solutions are currently being studied to avoid having resource to the use of wall-refined meshes. The first option consists in coupling a boundary layer code [10,11] to an Euler solver; the second being the development of a wall function approach in a Navier-Stokes environment.…”
Section: Introductionmentioning
confidence: 99%